Embodied communities : dance traditions and change in Java - Hughes-Freeland, Felicia, 1954- (Dance and performance studies, 2008)
Court dance in Java has changed from a colonial ceremonial tradition into a national artistic classicism. Central to this general transformation has been dance's role in personal transformation, developing appropriate forms of everyday behaviour and strengthening the powers of persuasion that come from the skillful manipulation of both physical and verbal forms of politeness. This account of dance's significance in performance and in everyday life draws on extensive research, including dance training in Java, and builds on how practitioners interpret and explain the repertoire. The Javanese ca.